Pengaruh Waktu Tunggu Terhadap Kepuasan Pasien pada Pemeriksaan USG di RSU Kertha Usada Buleleng - Febry Ivone Mamun; Cokorda Istri Ariwidyastuti (Vitamin : Jurnal ilmu Kesehatan Umum, 2025)
This study aims to analyze the effect of waiting time on patient satisfaction undergoing ultrasound examinations at Kertha Usada Buleleng General Hospital. A quantitative survey method was employed, involving 50 respondents. Data were collected using a questionnaire measuring waiting time and patient satisfaction levels. The results indicate that the average waiting time is 90 minutes, and there is a significant negative correlation between waiting time and patient satisfaction (r = -0.58, p < 0.05). Approximately 80% of patients reported being satisfied or sufficiently satisfied, while 20% expressed dissatisfaction. The study concludes that improved management of waiting times and enhanced service quality are essential for increasing patient satisfaction. Recommendations for the hospital include developing a more efficient waiting time management system and improving communication with patients.